2019
DOI: 10.3390/pr7120942
|View full text |Cite
|
Sign up to set email alerts
|

Colloids at Fluid Interfaces

Abstract: Over the last two decades, understanding of the attachment of colloids to fluid interfaces has attracted the interest of researchers from different fields. This is explained by considering the ubiquity of colloidal and interfacial systems in nature and technology. However, to date, the control and tuning of the assembly of colloids at fluid interfaces remain a challenge. This review discusses some of the most fundamental aspects governing the organization of colloidal objects at fluid interfaces, paying specia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 143 publications
0
15
0
Order By: Relevance
“…Thus, the relaxation process should be ascribed to the exchange of the lipid molecules between the LC and LE phase. However, the introduction of SiO 2 particles leads to a slowdown of the relaxation process for almost one order of magnitude [31]. This may be explained considering that the incorporation of SiO 2 particles hinders partially the phase coexistence as result of the stronger steric hindrance associated with the particles incorporation which modifies the lateral reorganization of the lipid molecules at the interface.…”
Section: Effect Of Particles' Incorporation In the Dilational Response Of Dppc Langmuir Monolayersmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the relaxation process should be ascribed to the exchange of the lipid molecules between the LC and LE phase. However, the introduction of SiO 2 particles leads to a slowdown of the relaxation process for almost one order of magnitude [31]. This may be explained considering that the incorporation of SiO 2 particles hinders partially the phase coexistence as result of the stronger steric hindrance associated with the particles incorporation which modifies the lateral reorganization of the lipid molecules at the interface.…”
Section: Effect Of Particles' Incorporation In the Dilational Response Of Dppc Langmuir Monolayersmentioning
confidence: 99%
“…The investigation of the impact of particles on lipid layers takes particular importance because several studies have provided evidence that the interaction of colloidal particles with surfactant layers modifies both the lateral organization and the mechanical of such surfactant layers [31][32][33]. Therefore, a strong modification of the physico-chemical behavior of biologically-relevant lipid layers as results of the particles incorporation may be expected [34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, any dysfunction in the normal performance or composition of the lung surfactant layer can affect the normal respiratory process, and simultaneously facilitate the penetration of pathogens' agents to other tissues [14]. This is particularly important because several studies have shown that particles can interact with fluid layers, altering their composition, lateral organization, and physico-chemical properties, especially the rheological one [15][16][17][18][19]. Therefore, the understanding of the interaction of particles with lung surfactant models is particularly important because it can help to deepen the potential impact of inhaled particles on the properties of this system, which may be useful as a preliminary tool for the evaluation of the potential toxicity of inhaled particles [20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…These emulsions offer as a main advantage their higher stability in relation to conventional ones due to the steric hindrance or electrostatic repulsions associated with the trapping of particles at the fluid/fluid interface, which prevents or at least minimizes the coalescence phenomena. Furthermore, particle adsorption at fluid/fluid interfaces is in most of the cases an irreversible process (trapping energy is much higher than thermal energy), which makes Pickering emulsions extremely stable emulsions [ 303 , 304 , 305 , 306 , 307 , 308 , 309 , 310 , 311 , 312 , 313 ]. The potential of Pickering emulsions as templates for LbL multilayers was proven by Li and Stöver [ 206 ].…”
Section: Lbl Multilayers On Emulsion Dropletsmentioning
confidence: 99%